2010
DOI: 10.1007/s12247-010-9078-y
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and Thermotropic Gelation of Aqueous Sodium Alginate Solutions

Abstract: In this work, we present the evaluation of the thermotropic gelling ability and steady-state rheology of aqueous sodium alginate (NaAlg) solutions. NaAlg is been considered due to its gelling capabilities and to determine its suitability as a film-forming agent with the potential capacity for immobilization of very potent, solid, and hydrophobic drugs. The existence of a thermally induced gelation of 1.0 to 2.5 wt.% sodium alginate solutions between 13°C to 22°C was demonstrated through three independent rheol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…We found the ratio to be close to 1 most of the time, which indicated that the epimerases functioned throughout the culture time. Similar values can be found in the literature . However, at the highest shaking frequency of 20 g the M/G ratio varied a lot, as we observed a larger standard deviation, probably indicating the widest variety of monomer distribution at that growth stage.…”
Section: Resultssupporting
confidence: 90%
“…We found the ratio to be close to 1 most of the time, which indicated that the epimerases functioned throughout the culture time. Similar values can be found in the literature . However, at the highest shaking frequency of 20 g the M/G ratio varied a lot, as we observed a larger standard deviation, probably indicating the widest variety of monomer distribution at that growth stage.…”
Section: Resultssupporting
confidence: 90%
“…[10][11][12][13][14] The thermodynamic and hydrodynamic properties of these charged polysaccharides are quite complex, with significant changes in molecular conformation, degree of entanglement, and rigidity in different ionic strength solutions. 15 For example, Florian-Algarin and Acevedo 16 showed that aqueous solutions of sodium alginate undergo thermally induced reversible gelation at concentrations between 1 and 2.5 weight percent, with a large hysteresis between gel formation and melting.…”
Section: Introductionmentioning
confidence: 99%
“…According to the available data in literature, the gelling process, for the Mg 2+ /alginate system, does not occur due to the weak polymer‐ion interactions ; in this study, a stable Mg 2+ /alginate gel was achieved using a solvent/nonsolvent system to collect the microspheres.…”
Section: Introductionmentioning
confidence: 98%